PENGARUH BRAND IMAGE DAN BRAND LOVE TERHADAP PURCHASE DECISION MELALUI WORD OF MOUTH (Pada pengguna Oppo Smartphone di Mbah Jo Malang) - Ana Laillaturovikoh; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT          This study aims to determine the effect of brand image and brand love on the purchase decision through word of mouth on Oppo Smartphone users at the Mbah Jo Malang counter. The population in this study took from data obtained from Oppo Smartphone counter users Mbah Jo Malang in February-April. Based on the samples taken from data obtained from the Oppo Smartphone Counter Mbah Jo Malang with the number of buyers in the last 3 months namely 1,309 customers. Sampling in this study was 93 respondents. The analytical method used is the Path Analysis method. The results in this study indicate that brand image (X1) has a positive significant effect on word of mouth (Z). And brand love (X2) is positive for word of mouth (Z). That brand image (X1) has a significant positive effect on purchase decision (Y). for brand love (X2) positive for purchase decision (Y). And word of mouth (Z) has a significant positive effect on purchase decision (Y).  Keyword: Brand Image, brand Love , Purchase Decision, Word Of Mouth